Assessment of Health-Seeking Behavior on Maternal and Child Health among Nursing Mothers in Public Primary Health Care Centres in Kwara State, Nigeria (Federal University Gusau Faculty of Education Journal, 2026)
This study investigated the effects of flipped classroom methods on secondary school students' performance in biology class in Kaduna Metropolis. The research employed a quasi-experimental design with a sample of 80 senior secondary school students selected from public secondary schools. The study examined three research questions focusing on the difference in performance between students taught using flipped classroom methods and those taught using traditional methods, the influence of gender on performance, and the impact of school type on learning outcomes. Data were collected using a Biology Achievement Test and analyzed using descriptive statistics, independent t-test, and one-way ANOVA. Results revealed that students taught using flipped classroom methods significantly outperformed those taught using traditional methods (t = 4.68, p < 0.05). Gender differences were not statistically significant (t = 1.23, p > 0.05), while school type showed significant variation in performance (F = 6.45, p < 0.05). The study concluded that flipped classroom methods are more effective than traditional teaching methods in improving students' biology performance. Recommendations include training teachers on flipped classroom implementation and providing adequate technological infrastructure in schools.